Entrepreneurial perspective of the circular economy: Origin and principles towards a sustainable world - Nson, Yilkes Danladi; Adejoh , Abimaje Solomon (goodwood publishing, 2025)
Purpose: This paper aims to add to the discourse on circular economy by further explaining the concept of CE and its application in entrepreneurship and business to ensure a cleaner environment in quest of a sustainable world. Research Methodology: This study adopted in-depth qualitative exploratory review of relevant work related to the scope of the study. The study collected secondary data from relevant materials including articles, conference papers, company publications, theses, books, periodicals and other documents available on the internet. Results: The study findings argue that CE system centers around a regenerative, and restorative economic system, anchored on 7Rs principles. Businesses, entrepreneurs, government and policy makers must be mindful of the importance of CE to ensure responsible sustainable production and consumption in quest of a sustainable world. Conclusions: The study concludes that the adoption of CE plays a key role in achieving economic stability, environmental protection, social well-being, thereby accelerating SDGs. Limitations: This study is limited to the concept of CE, principles and application in pursuit of economic stability, environmental protection and social well-being as well as achieving sustainable world. Contributions: This study will aid organizations, researchers, entrepreneurs, government, and community leaders to develop and implement policies that will ensure a cleaner environment for a sustainable future for all.